DEVELOPMENT OF AN INTELLIGENT CAT SAND BASIN - Joseph, Ann Joann (2017)
In the field of cat health monitoring, collecting real time data is vital. A system that can remotely monitor the health of a cat through the measurement of weight of the cat, behavior based on the time the cat spend in sand basin and also count the number of visit for up to 2 cats per sand basin to monitor regular or irregular behavior is presented in this paper. The data was collected from a survey study from pet owners, consultation from veterinarians and experiment conducted on 4 pet cat and known weights which is used to represent the cats of various weight, with the aid of sensors developed to test the system. Arduino micro-controller is programmed to collect data from the sensors and transmit the data wirelessly to a host PC using Wi-Fi module for real time update into a IoT platform namely BLYNK. The system developed is purposed to monitor the health of feline regularly, detect any distress sign by analyzing behavior chart on how long the feline spend time in the basin and number of visit of feline to the sand basin per day. Early detection of change in behavior and weight is vital to prevent incurable diseases, long term medication and even unnatural death.